When the designed space meets the lived space. The territorial development projects as complex processes of «translation» - de Reymaeker, Brice (Documents d’Anàlisi Geogràfica, 2012)
In the present article the theoretical lines and the successive methodological proposals that guide my attempt to study the projects of cooperation for territorial development, under a geographic approach inspired by social constructivism, are presented. After presenting those projects like dynamic wholes in relation between themselves of spatial conceptions, practices and representations, different essential contributions of postcolonial and feminist geography as well as of the no representational perspective are reviewed. In fact those contributions may serve as departure point for the conceptualization, in a more subtle way, of the process of translation or negotiation that occurs not only between the different actors engaged in the territorial development projects but also between their different conceived, perceived and lived spaces.